2021
DOI: 10.1371/journal.pone.0261245
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference of local government audit outcomes

Abstract: The scandals in publicly listed companies have highlighted the large losses that can result from financial statement fraud and weak corporate governance. Machine learning techniques have been applied to automatically detect financial statement fraud with great success. This work presents the first application of a Bayesian inference approach to the problem of predicting the audit outcomes of financial statements of local government entities using financial ratios. Bayesian logistic regression (BLR) with automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The results of the present study demonstrated that step-wise regression selects variables that capture the most variation in data better than those selected using random forest or correlation analysis. We further find that debt to operating ratio, current ratio and net operating surplus margin are the most important variables in predicting audit outcomes, which are in line with the results of [1,12].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The results of the present study demonstrated that step-wise regression selects variables that capture the most variation in data better than those selected using random forest or correlation analysis. We further find that debt to operating ratio, current ratio and net operating surplus margin are the most important variables in predicting audit outcomes, which are in line with the results of [1,12].…”
Section: Resultssupporting
confidence: 86%
“…This is particularly important in South Africa where little research has been conducted, especially in the local government sphere. Our work expands on that of Mongwe and Malan [1] and Mongwe et al [12] in that we present a first-in-the-literature comparison of various machine learning algorithms and feature selection techniques for the task of analysing audit outcomes of South African municipalities. The results of this study could prove to be useful to the various users of financial statements, particularly as we also highlight which variables are important in discriminating between financial statements with qualified and unqualified audit opinions.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations